Electromagnetic Characteristics of the Simplest Strip System - Koshovy, G.I. (Радиофизика и радиоастрономия, 2003)
The main electromagnetic characteristics of the noncoplanar system of two narrow strips with parallel edges are investigated. They are determined on the basis of the integral equation technique, using the local coordinate systems. Analytical expressions of the longitudinal and transverse surface current densities are presented. They are validated by passing to the limit of a single strip and allow both analytic and numerical examination of the strip interaction. By using the obtained expressions, the field in the far zone, the scattering cross section and the scattering coefficient are deduced. These expressions are sufficiently simple and convenient for numerical calculation. Досліджено основні електромагнітні характеристики найпростішої некомпланарної системи вузьких стрічок з паралельними краями. Вони отримані на основі методу інтегральних рівнянь з використанням локальних координатних систем. Наведено аналітичні вирази для густини поздовжніх та поперечних поверхневих струмів. Вони були успішно перевірені граничним переходом до однієї стрічки і дозволяють дослідити як аналітично, так і числовими методами взаємовплив стрічок. На основі цих виразів знайдено асимптотичні вирази для поля у дальній зоні, поперечного перерізу розсіювання та коефіцієнта розсіювання. Отримані аналітичні вирази є достатньо простими і зручними для числового обрахунку. Исследованы основные электромагнитные характеристики простейшей некомпланарной системы узких полосок с параллельными краями. Они получены на основе метода интегральных уравнений с использованием локальных координатных систем. Приведены аналитические выражения для плотности продольных и поперечных поверхностных токов. Они были успешно проверены предельным переходом к одной ленте и позволяют исследовать как аналитически, так и численно взаимовлияние лент. На основе этих выражений найдены асимптотические выражения для поля в дальней зоне, поперечного сечения рассеяния и коэффициента рассеяния. Полученные аналитические выражения достаточно просты и удобны для численных расчетов.